Emotional Intelligence in Teacher Education: An intervention study in Greece - Kyriazopoulou, Myrto (2020)
Emotional Intelligence (EI) of teachers has been associated with positive assets both personal and professional (Corcoran & Tormey, 2013; Vesely, Saklofske & Leschied, 2013), which should be developed in teacher education (Dacre-Pool & Qualter, 2012). Despite its commonly accepted importance, only a few studies have focused on EI in the context of teacher education (Gilar-Corbi, Pozo-Rico, Pertegal-Felices & Sanchez, 2018), few of which have had mixed method designs (Hen & Sharabi-Nov, 2014), while none have been conducted in Greece. The purpose of this study was to examine the effectiveness of an interven-tion regarding the development of EI and to get insights into student teachers’ experiences, emotions and perceptions. The study followed a quasi-experimental mixed-method convergent design using the Trait Emotional Intelligence Ques-tionnaire (TEIQue SF, Greek version) and emotion diaries. Participants were stu-dents from the University of Crete (N=42, 21 in intervention, 21 in control), stud-ying the bachelor’s program of Primary education and teaching. The intervention was 2 weeks long (4 hours total) and focused on the four-branch model (Salovey & Mayer, 1997). Only the intervention participants wrote emotion diaries (N=19). The analysis of EI using TEIQue SF (pre and post-tests) indicated no significant change in EI in intervention or control group. The themes that emerged from the thematic analysis of emotion diaries were emotion regu-lation and identification, self-awareness and intervention talk. From the integra-tive findings, it could be implied that longer intervention could have more im-pact, while both ability and trait instruments should be utilized in measuring EI.